Penerapan Kurikulum Merdeka Dan Platform Merdeka Belajar Untuk Mewujudkan Kualitas Pada Pendidikan - Salma Jasmine Kamal; Hindun Hindun (Pusat Riset dan Inovasi Nasional, 2023)
This research aims to determine the application of the independent curriculum and the independent learning platform to realize quality in education. It is hoped that the Independent Curriculum provides significant flexibility for students and teachers. The Merdeka Belajar Platform, is the technology supporter. As well as discussing the implementation of the Independent Curriculum and the Independent Learning Platform to improve the quality of education in Indonesia. The method used in this research is literature study and is descriptive. This research data was obtained from various literature, several scientific references, in the form of books and scientific journal articles. The results of this research are (1) Teacher Application in Developing Learning Curriculum. (2) Application of the Independent Curriculum to Improve Learning. (3) Implementation of the Merdeka Belajar Platform as a Learning Support.